The clinical impact of 16S ribosomal RNA PCR and sequencing in the identification of bacterial infections: a 7-year report from a Lebanese tertiary care center - Youssef, Nour; Boutros, Celina F.; Dakroub, Fatima; Akl, Fata; Reslan, Lina; Finianos, Marc; Moumneh, Mohammad Bahij M.; Dargham, Tarek Bou; Zein, Zeinab El; Haddara, Amani; Korman, Rawan; Khafaja, Sarah; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe identification of bacterial pathogens in the clinical setting is essential for providing optimal care and improving outcomes. The primary objective of this study was to assess the performance of the 16S test in bacterial identification from different samples and determine its impact on clinical outcomes.MethodsThis was a retrospective study of patient samples collected from all age-groups at the American University of Beirut Medical Center (AUBMC), from May 2016 to December 2022. Descriptive statistics were conducted to calculate the 16S test positivity rate and to describe the different types of organisms. Univariate analyses were performed to study the clinical impact of the 16S test and its comparison to the conventional bacterial culture among different characteristics. A p ≤ 0.05 was considered statistically significant.ResultsA total of 1489 specimens were submitted for the 16S test during the study period. Of the submitted tests, 395 (26%) had bacteria identified by the 16S test and/or culture. Out of the culture negative/16S positive group, the majority were from specimens collected from the skin and soft tissue system (24 out of 92, 26.1%). This was followed by musculoskeletal specimens (15 out of 92, 16.3%), and central nervous system specimens (14 out of 92, 15.2%). Pus samples had a positivity rate of 66.3% with 5 times higher odds of being positive compared to non-pus samples (25%). Overall, there were 260 identified organisms by 16S test of which the most detected organisms were Staphylococcus spp, Streptococcus spp. and Enterobacterales. The results revealed that 16S testing impacted management in 45.9% of the cases (83/181) showing a change in management. Antibiotic escalation was applied in 31.3% of cases (26/83). Antibiotic de-escalation occurred in 41% of cases (34/83). A change in the treating diagnosis was noted in 26.5% of cases (22/83).ConclusionIdentification of pathogens using the 16S test in combination with conventional cultures is essential in clinical diagnostics and management of infectious diseases to provide targeted therapy and improve antimicrobial stewardship. Shorter turnaround time, improved patient management, and cost-effectiveness are key factors to consider when advocating for the broader adoption of 16S testing.